Temporal trend of accidents due to percutaneous exposure in a public hospital in Brazil, 2007-2019 - Renan Sallazar Ferreira Pereira; Cecília Angelita dos Santos; Adriano Marçal Pimenta (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the temporal trend of accidents due to percutaneous exposure in a public hospital in Brazil, between 2007 and 2019, according to sociodemographic and professional characteristics. Methods: analysis of time series of accidents due to percutaneous exposure that occurred in health workers. Sociodemographic and professional variables, accident profile, post-accident behavior and accident incidence rates were evaluated. The Prais Winsten regression was used for trend analysis and calculation of the annual percentage change, with a significance level of 5%. Results: 761 occupational accidents were recorded. There was a downward trend in the rate of percutaneous injuries among female workers (-0.012%; p=0.009), who had secondary education (-0.011%; p=0.035) and among all health professional categories (-0.010%; p =0.019). There was an increasing trend (0.018%; p= 0.050) among workers with ≥ 61 months of professional experience. Conclusions: the analysis showed a decreasing incidence of percutaneous accidents, which can be explained by multiple factors.